Regional integration in Latin America: Comparative theories and institutions - Malamud,Andrés (2004)
Regional integration in Latin America is a long but not-so-successful story. Only by 1990 the creation of a new regional bloc - namely Mercosur - and the relaunching of two previous attempts - the Andean Community of Nations and the Central American Common Market - allowed to envision a different trend. Today, the three referred blocs feature a series of divergent characteristics, among them the reached level of integration and the type of institutionalization. However, all three have something in common: none fits easily the theories of regional integration that were developed drawing on the European case. This paper analyzes the Latin American integration experience in light of the main contemporary integration theories, in order to pinpoint some inconsistencies between theories and cases with a view to guiding further research. Among the main findings is the increasing relevance of national executives as crucial driving force of the integration processes.